Using the Pythagorean theorem, we can substitute the given values into the formula.
a^2 + b^2 = c^2
76^2 + 30^2 = c^2
5776 + 900 = c^2
6676 = c^2
Therefore, c^2 is equal to 6676.
apply the Pythagorem theorem to this answer
a2 + b2 = c2
76^2 + 30^2 = c^2 f
3 answers
dont forget to square it!
Apologies for the oversight. Let's correct it.
Using the Pythagorean theorem, we can substitute the given values into the formula.
a^2 + b^2 = c^2
76^2 + 30^2 = c^2
5776 + 900 = c^2
6676 = c^2
Taking the square root of both sides:
c = √(6676)
Therefore, c is approximately equal to 81.75 (rounded to two decimal places).
Using the Pythagorean theorem, we can substitute the given values into the formula.
a^2 + b^2 = c^2
76^2 + 30^2 = c^2
5776 + 900 = c^2
6676 = c^2
Taking the square root of both sides:
c = √(6676)
Therefore, c is approximately equal to 81.75 (rounded to two decimal places).